2015
DOI: 10.1037/xlm0000118
|View full text |Cite
|
Sign up to set email alerts
|

Can arousal modulate response inhibition?

Abstract: The goal of the present study was to examine if and how arousal can modulate response inhibition. Two competing hypotheses can be drawn from previous literature. One holds that alerting cues that elevate arousal should result in an impulsive response and therefore impair response inhibition. The other suggests that alerting enhances processing of salient events and can therefore enhance processing of a cue that indicates to withhold a response and improve response inhibition. In a stop-signal task, participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 37 publications
2
24
2
Order By: Relevance
“…Here, it could be argued that the beneficial effect of alerting signals cannot be attributed solely to an influence on response selection, because there is no selection between two response options in these tasks (but see Gomez, Ratcliff, & Perea, 2007, for evidence that go-no-go tasks may be a special variant of response selection tasks). Instead, an alerting effect on response speed without an increase in error rates might be better explained in terms of a perceptual processing benefit (see also Weinbach, Kalanthroff, Avnit, & Henik, 2015). In line with this alternative explanation, a variety of studies investigating alerting effects outside of conflict paradigms have shown that alerting signals modulate indicators of perceptual processing.…”
Section: Discussionmentioning
confidence: 92%
“…Here, it could be argued that the beneficial effect of alerting signals cannot be attributed solely to an influence on response selection, because there is no selection between two response options in these tasks (but see Gomez, Ratcliff, & Perea, 2007, for evidence that go-no-go tasks may be a special variant of response selection tasks). Instead, an alerting effect on response speed without an increase in error rates might be better explained in terms of a perceptual processing benefit (see also Weinbach, Kalanthroff, Avnit, & Henik, 2015). In line with this alternative explanation, a variety of studies investigating alerting effects outside of conflict paradigms have shown that alerting signals modulate indicators of perceptual processing.…”
Section: Discussionmentioning
confidence: 92%
“…However, in the Stop-signal task, which measures a more global form of response inhibition, Stop-signal reaction time (SSRT) was significantly slower in the temporal versus neutral condition. This result could be due either to faster SSRTs in the neutral condition (Weinbach et al, 2015) or slower SSRTs in the temporal condition. In parallel, response times to go targets were significantly faster in the temporal versus neutral condition.…”
Section: Discussionmentioning
confidence: 95%
“…Many previous studies of response inhibition have shown that presentation of non-specific warning cues in the Flanker paradigm increases interference effects, due either to a deleterious effect on cognitive control (e.g., Callejas, Lupiàñez, Funes, & Tudela, 2005) or to enhanced sensory processing of irrelevant, as well as relevant, stimuli (e.g., Nieuwenhuis & de Kleijn, 2013;Weinbach & Henik, 2012b). Indeed, enhanced sensory processing has also been used to explain the beneficial effects of warning cues in the Stop-signal paradigm (Weinbach, Kalanthroff, Avnit, & Henik, 2015). These authors have also made a clear distinction between warning cues (a non-specific state of alertness before target onset) and temporal cues (prediction of target onset) (Weinbach & Henik, 2012a, 2013, and suggested that each might influence processing in similar, yet independent, ways.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the SSRT results revealed that threat impaired the ability to inhibit activated responses (see e.g., Herbert & Sütterlin, 2011;Kalanthroff et al, 2013;Pessoa et al, 2012 experiment 2;Rebetez et al, 2015;Verbruggen & De Houwer, 2007;Yu et al, 2012 for comparable findings). Although this effect is not always observed in behavioral experiments (see e.g., Pawliczek et al, 2013;Pessoa et al, 2012 experiment 1;Sagaspe et al, 2011;Senderecka, 2016;Weinbach et al, 2015), it is in line with THREAT, SLEEP DEPRIVATION AND RESPONSE INHIBITION 19 neurobiological models suggesting that acute threat causes a decrease in prefrontal cognitive control functions (see e.g., Bishop, 2008;Hermans et al, 2014). The fact that we did find impaired stop-signal response inhibition under threat while others did not, may be due to the intensity of our threat manipulation.…”
Section: Effects Of Threat On Shooting Decisions and Response Inhibitionmentioning
confidence: 93%